Pancreatic malignancy in the backdrop of chronic pancreatitis: How much to push the boundaries to achieve R0 resection - Joshi Kunal Sadanand; Bodepudi Sisir; Ganapathi Santhosh Kumar; Murugesan Chandrasekar; Balu Jagan; Subramanian Sankar (Forum of Clinical Oncology)
Tumors of the body and tail of the pancreas are often more aggressive than tumors of the head and would have often undergone metastatic spread to other organs at the time of diagnosis. Most patients with carcinoma of the body and tail of the pancreas present at a late stage. Surgery is only indicated in those patients in whom there is no evidence of metastatic spread. Surgery is often not possible in cancers of the body and tail of the pancreas if the tumor invades celiac artery. Controversy exists regarding the margin status impact of microscopic resection margin involvement (R1) after pancreaticoduodenectomy (PD) for PDAC. There are reports indicating the rate of R1 resections increases significantly after PD if pathological examination is standardized. In this report, we present the case of a 56-year-old female who had undergone lateral pancreaticojejunostomy for chronic pancreatitis 8 years ago, but has now developed malignancy of the body and tail of the pancreas involving multiple organs. This patient underwent en bloc resection involving: 1. distal pancreatectomy with jejunal loop (lateral pancreaticojejunostomy) resection; 2. splenectomy; 3. left nephrectomy; 4. total gastrectomy; and 5. segmental colectomy with reconstruction by esophagojejunostomy, jejunojejunostomy, and colocolic anastomosis. The infrequent occurrence of tumor in the distal gland and advanced tumor stage at the time of diagnosis have both combined to produce therapeutic nihilism/dilemma in the minds of many surgeons. This report highlights the decision on how much to the push limits for multi-organ resection (en bloc resection with distal pancreatectomy, gastrectomy, splenectomy, colectomy, nephrectomy) with the intent of achieving R0 status in spite of the complexity of surgery in selected patients.